Coupling an artificial receptor with macrophage membrane for targeted and synergistic treatment of cholestasis - Qiaoxian Huang; Zong-Ying Hu; Shuwen Guo; Dong-Sheng Guo; Ruibing Wang (Supramolecular Materials, 2022)
Cholestasis is defined as an impairment of bile acid flow leading to intrahepatic retention of toxic bile acids (BAs), which induce apoptosis or necrosis of hepatocytes and liver inflammation. Ursodeoxycholic acid (UDCA), a FDA-approved drug to treat cholestasis, has limited therapeutic effects due to its poor specificity. Herein, we report a targeted therapeutic platform (namely, MAP) based upon co-assembly of macrophage membrane and amphiphilic calix[4]arene on PLGA nanoparticles. With UDCA loaded into calix[4]arene on the surface, MAP exhibited long-term stability, excellent biocompatibility, prolonged retention in the inflammatory liver due to the homing effects of macrophage membrane, and effective therapy of cholestasis via the specific action of UDCA and efficient sequestration of toxic BAs and inflammatory cytokines by the artificial receptor and membrane receptors, respectively. This study not only provides an artificial receptor coupled macrophage-mimetic nanomedicine platform to conquer cholestasis but also offers new insights into the design of improved versions of biomimetic nanomaterials that harness the power of both the natural and artificial receptors.